Red fox NimbleGen SeqCap EZ_probes - Donaldson, Michael E.; Rico, Yessica; Hueffer, Karsten; Rando, Halie M.; Kukekova, Anna V.; Kyle, Christopher J. (Dryad Digital Repository, 2017)
Coordinates used to design the overlapping NimbleGen SeqCap EZ probes.